Initial visioning and planning for policy change with partners and other BDC projects - Miah, M A Hamid (2012)
The objectives are this vision document are to: 1) suggest guidelines and steps towards deiserble policy shifts; 2) compile an understanding of the issues and probable technical solutions that require appropriate policy shifts, based on the experiences of different development partners working in these areas; and 3) envision outcomes for the four components of the GBDC.